2017
DOI: 10.5424/sjar/2017152-10317
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interaction for fertility and milk yield traits in Canadian, Mexican and US Holstein cattle

Abstract: The objective of this study was to evaluate genotype × environment interaction (G×E) between Canada, the United States and Mexico for fertility and milk yield traits using genetic correlations between countries estimated from genetic evaluations of sires. Genetic correlation between Mexican and Canadian Holsteins for age at first calving was ≤ 0.48 and lower than the simulated value obtained accounting for data structure and selection effects. For calving interval, genetic correlation between Mexico and Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
5
0
4
Order By: Relevance
“…In the genetic selection process, this trait could have slower genetics gain in the region with low heritability than in regions of moderate heritability. Similar values have been reported by Montaldo et al (2017) and Tullo et al (2014) for herds of Holstein cattle in Mexico and Italy, respectively. This indicates that temperature has a negative effect on PY heritability, which is consistent with that reported by Carabaño et al (2014) for herds in Spain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the genetic selection process, this trait could have slower genetics gain in the region with low heritability than in regions of moderate heritability. Similar values have been reported by Montaldo et al (2017) and Tullo et al (2014) for herds of Holstein cattle in Mexico and Italy, respectively. This indicates that temperature has a negative effect on PY heritability, which is consistent with that reported by Carabaño et al (2014) for herds in Spain.…”
Section: Discussionsupporting
confidence: 88%
“…Similar values have been reported by Montaldo et al . (2017) and Tullo et al . (2014) for herds of Holstein cattle in Mexico and Italy, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…König et al, 2005;Haile-Mariam et al, 2008), but also across country borders (e.g. Montaldo et al, 2017). König et al (2005) only identified indications for G × E interactions when considering several environmental descriptors simultaneously, for example, herd location and herd size.…”
Section: Breeding Approaches To Improve Robustness In Dairy Cowsmentioning
confidence: 99%
“…There are reports which established uncertainty in the performance of genetically superior animals when subjected to a new environment ( 38 , 39 ). Genotype × environment interaction (G × E) studies help to evaluate the level of this uncertainty and can predict the extent to which an animal may perform in the new environment ( 38 ). This interaction arises when different environments unevenly influence the different genotypes ( 40 ).…”
Section: Genotype × Environmental Interaction and Evolutionary Changes On Dairy Cattle Population In Hot Conditions: From Quantitative Gementioning
confidence: 99%
“…This interaction arises when different environments unevenly influence the different genotypes ( 40 ). Therefore, it is necessary to understand the production environment before making a selection policy since the interactions between genetic and environment may hamper the performance efficiency of the animal ( 38 , 40 ). High-yielding dairy cows derived from temperate regions, for example, have failed to express their productive potential when imported to be raised under tropical conditions ( 41 ).…”
Section: Genotype × Environmental Interaction and Evolutionary Changes On Dairy Cattle Population In Hot Conditions: From Quantitative Gementioning
confidence: 99%